Six-hierarchy model of accident analysis and its application in coal mine accidents - Qiuju Ma; Mengsai Wan; Juncheng Shao; Mingyu Zhong; Yuhao Guo; Wei Wang (Journal of Safety Science and Resilience, 2022)
Accident analysis models play a significant role in accident investigation and analysis. Most traditional models, usually based on a chain of events, have serious limitations when used for complex systems, especially for coal mine accident. HFACS is a widely accepted accident cause model with complex structure and content. Based on HFACS and accident investigation need in China, a new systemic accident analysis method “Six-hierarchy model” is proposed. And the index database of accident causal factors at each hierarchy of coal mine accidents is established. This model provides clear guidance for the prevention of accidents from six levels, which helps to the targeted rectification after accidents and the improvement of safety management level. The source, application scope, advantages and disadvantages of HFACS and six-hierarchy model are compared. The “2.14” gas explosion accident in Sunjiawan coal mine is analyzed by using HFACS and six-hierarchy model and the safety management suggestions are put forward. The study shows that the Six-hierarchy model provides a clear guide for the prevention of accidents from six levels. And it benefits the targeted rectification after accidents and the continuous improvement of safety management.